(untitled) (ACME, 2023)
The only surviving astronomical poem of Hellenistic age are the Aratus’ Phaenomena. Little is known about non-Aratean astronomical poetry of which scanty evidence and fragmentary examples remain, including the five hexameters on the moon by Hegesianax (SH 466-467). This contribution aims to assess the position of Hegesianax within didactic poetry on astronomical subjects. The paper considers the testimony on his astronomical production and analyses both the context of the quotation and the text of the fragments.